Formation of Food Clusters in Europe - Völgyiné Nadabán, Márta (Acta Agraria Debreceniensis, 2011)
In the dictionary of foreign words and phrases we can find the word “cluster” with the following sense: aggregation, group and in a wider meaning: association, integration. By explaining the geographical concentration of economical and innovation processes in the food processing sector, clusters, and especially business clusters, play an important role. This essay deals exclusively with business clusters, so the term cluster is used also for business cluster. I tried to collect the most relevant indicators determining the formation of clusters in the Food Processing Sectors and to analyze whether a correlation can be found among the analyzed indicators.